The 20th century children's poetry treasury - Prelutsky, Jack; So, Meilo (New York : Alfred A. Knopf, 1999)
A collection of more than 200 poems by such modern poets as Nikki Grimes, John Ciardi, Karla Kuskin, Ted Hughes, e.e. cummings, Eve Merriam, Deborah Chandra, Arnold Adoff, and more than 100 others.
Includes index.
Keywords: Children's poetry, American; American poetry -- 20th century; English poetry -- 20th century; Children's poetry, English; American poetry -- Collections; English poetry -- Collections